ANGLO-AMERICAN ENCOUNTERS AND THE EVOLUTION OF CULTURAL INDEPENDENCE IN 19TH-CENTURY AMERICAN LITERATURE (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article explores the complex process through which American literature achieved cultural independence during the 19th century, focusing on the dynamic interplay known as Anglo-American encounters. Although the United States secured political independence in 1776, its literary culture remained heavily influenced by British traditions well into the early 19th century. The study aims to investigate how American writers gradually moved from imitation to innovation, ultimately establishing a distinct national literary identity.